PHYSICAL BASIS OF PROTON RADIATION THERAPY IN MEDICINE - Elmurotova Dilnoza Baxtiyorovna; Odilova Nilufar Jurayeva; Jumanov Shokir Eshimovich; Odilova E‘zoza Ulug‘bek qizi (Bright Mind Publishing, 2025)
The work considers the history of using proton irradiation in medicine and the disadvantages of photon radiation therapy. The physical basis of proton therapy is shown according to the graph of tissue proton absorption, in which the Bragg peak's position can be adjusted using proton energy. It is shown that proton therapy for the treatment of lung cancer is one of many therapies, due to its unique physical and biological properties.
Keywords: Proton, therapy, tumor, safety, photon, tissue, Bragg peak, cancer, physics, beam.